A study of biodiesel production from algae - Ricky, Stu Anding (Universiti Malaysia Sarawak (UNIMAS), 2009)
Biodiesel is a biodegradable fuel which produces lower CO2 and NOx emissions. Continued use of petroleum sourced fuels is now widely recognized as unsustainable due to depleting supplies and the contribution of these fuels to the accumulation of carbon dioxide in the environment. Renewable and carbon neutral transport fuels are necessary for environmental and economic sustainability. Biodiesel derived from oil crops is a potential renewable and carbon neutral alternative to petroleum fuels. Unfortunately, biodiesel from oil crops, waste cooking oil and animal fat cannot realistically satisfy even a small fraction of the existing demand for transport fuels. Algae have emerged as one of the most promising sources for biodiesel production. Like plants, algae use sunlight to produce oils but they do so more efficiently than crop plants. Oil productivity of many algae greatly exceeds the oil productivity of the best producing oil crops. It can be inferred that algae grown in CO2 with enriched air can be converted to oily substances. Such an approach can contribute to solve major problems of air pollution resulting from CO2 evolution and future crisis due to a shortage of energy sources. As demonstrated here, algae appear to be the source of renewable biodiesel that is capable of meeting the global demand for transport fuels. This study was undertaken to know the proper transesterification process, amount of biodiesel production (ester), physical properties of algae biodiesel and algae biodiesel performance in a real diesel engine. With the used of biodiesel to replace normal diesel to run the diesel engine, there is a slight decrement in break horse power and a slight increment in the specific fuel consumption.